DAYA DUKUNG JERAMI JAGUNG SEBAGAI PAKAN TERNAK SAPI POTONG - Syaiful Umela; Nurfitriyanti Bulontio (Jurnal Technopreneur (JTech), 2016)
Trend increased consumption of meat in Indonesia showed a significant increase, in line with population growth, increasing income and economic status of the people of Indonesia. This trend is reinforced by the quality of Indonesian human resource education that is directly proportional to the awareness of the importance of consuming protein in meeting nutritional needs, especially protein. Beef as one of the best sources of animal protein, requires the support of fodder availability continuously. A potential source of feed material in the region of Gorontalo is corn straw. Potential forage crop waste is not used optimally. In the corn harvest season, the amount of this waste is abundant and mostly just dumped and burned. Waste forage maize, can be given directly to livestock and can also be in processed form, such as hay and silage. The processed waste can be stored forage longer to be used / consumed in the dry season / dry season when grass field difficult to obtain. Beef as ruminant livestock forage in a day can consume as much as 10 percent of their body weight. The number of large forage needs must always be available every day continuously.To support the development of beef cattle in Pohuwato, particularly in the provision of feed ingredients, necessary to identify the potential availability of green fodder from waste food crops derived from corn. This identification can predict how the carrying capacity of the feed derived from corn straw, so that local governments can calculate how the number of animals that can be accommodated and assured continuously feed needs.This study aimed to analyze the carrying capacity of corn straw as animal feed for beef cattle breeding business in Pohuwato. The Targets of this research is knowing the carrying capacity of corn straw as feed for cattle in Pohuwato.